2017
DOI: 10.1111/2047-3095.12177
|View full text |Cite
|
Sign up to set email alerts
|

Concept Analysis of Posttraumatic Stress Disorder

Abstract: A model case, borderline case, and contrary case of PTSD are provided. Discussion of the importance of a lack or loss of meaning in PTSD is included, along with exploration of transformative learning theory to inform clinical practice for nurses addressing a disruption of meaning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Sekhon performed a concept analysis on PTSD using Walker and Avant’s method from a nursing perspective, suggesting the five attributes of a triggering event or events, re-experiencing, fear, helplessness, and loss or lack of meaning [ 31 ]. Similarly, Nayback conducted a concept analysis of PTSD using Walker and Avant’s method indicating the attributes of re-experiencing, hyperarousal, and avoidance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sekhon performed a concept analysis on PTSD using Walker and Avant’s method from a nursing perspective, suggesting the five attributes of a triggering event or events, re-experiencing, fear, helplessness, and loss or lack of meaning [ 31 ]. Similarly, Nayback conducted a concept analysis of PTSD using Walker and Avant’s method indicating the attributes of re-experiencing, hyperarousal, and avoidance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Veterans with PTSD often have episodes of flashbacks or nightmares due to intrusive memories of traumatic events. Re-experiencing or reliving memories is a hallmark sign of PTSD [ 31 ]. This leads to unwanted upsetting memories and emotional distress [ 5 ].…”
Section: Defining Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Chapter 3, we found that individuals confronted with a violent loss, the loss of close kin, and a low level of education are more likely to develop comorbid PGD, PTSD, and depressive symptoms compared to individuals with other sociodemographic and loss-related characteristics. This means that co-morbidity of PGD, PTSD, and depression symptoms is not exclusively connected to a traumatic loss, as has been previously suggested by, among others, ), van Denderen et al (2015 and Boelen, Olff, and Smid (2019). Therefore, it is important to assess symptoms of all three disorders in bereaved individuals, regardless of the cause of the loss.…”
Section: Consequences Of Traumatic Lossmentioning
confidence: 87%
“…This information might be beneficial for the further development of models of care such as the stepped model for traumatic grief (Boelen, 2016;Boelen et al, 2019) or the three-tiered approach to bereavement care of Aoun et al (2015). In these stepped-care model, stages of increasing severity in PGD complaints are defined and risk factors and treatment options are offered.…”
Section: Discussionmentioning
confidence: 99%